Analisis Strategi Komunikasi dalam Meningkatkan Kinerja Aparatur Desa di Desa Ciburuy Kecamatan Padalarang Kabupaten Bandung Barat - Khoerunisa, Fahra; Makmur (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the communication strategies implemented in improving the performance of village officials in Ciburuy Village. Effective communication is very important in village governance to ensure good coordination between the village head, village officials, and the community. The research method used is qualitative research with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that the communication strategies implemented in Ciburuy Village are quite effective in improving the performance of village officials. Some of the communication methods used include regular meetings, the use of WhatsApp groups, the "Simple Desa" application, and village information boards. Two-way communication between the village head and village officials creates a more harmonious work environment, where village officials feel more appreciated and more responsible in carrying out their duties. In addition, the use of technology in communication helps accelerate the dissemination of information and improve work coordination. With the implementation of more effective communication, it is hoped that the performance of village officials in Ciburuy Village will continue to improve so that services to the community are increasingly optimal and village development can run more efficiently.